Understanding Patterns of Gender-Based Violence: Victim–Perpetrator Dynamics within a Social-Ecological Framework in Sarawak - Ke Lin, Siew; Shirly Siew Ling, Wong; Keng Sheng, Chew; Vanitha, Kandasamy (RSIS International, 2025)
Gender-based violence (GBV) is a pervasive issue that manifests in various forms that are often influenced by the relationship between the victim and the perpetrator. While intimate partner violence (IPV) is widely recognized, abuse by other family members, such as parents, siblings, or children, also presents serious concerns, particularly within households. Understanding the dynamics between victims and perpetrators is crucial for determining the nature and intensity of violence. This study investigates how the nature of the perpetrator-victim relationship affects the form and severity of GBV, with a focus on cases reported at the One Stop Crisis Center (OSCC) in Sarawak General Hospital. A total of 139 adult victims were surveyed between March 2021 and March 2023 using the World Health Organization's Violence Against Women Instrument (VAWI), which measures psychological, physical, and sexual violence. The analysis revealed that the relationship with the perpetrator significantly influenced the severity and type of violence experienced. Victims of intrafamilial violence were more likely to report experiencing only one form of abuse, whereas those subjected to IPV were more often exposed to multiple forms of violence. Although the demographic factors such as age, marital status, and education level showed some associations with the patterns of abuse, the perpetrator relationship remained the strongest predictor in this study. In fact, these findings highlight the importance of addressing GBV within both intimate and familial contexts. Understanding the dynamics of different relationships can inform more effective prevention strategies and support services that promote safety and resilience for individuals and communities in Sarawak.